1986
DOI: 10.1002/mmnz.19860620209
|View full text |Cite
|
Sign up to set email alerts
|

Bionomics of Trioxys (Binodoxys) indicus Subba Rao & Sharma, an Aphidiid Parasitoid of Aphis craccivora Koch. 20. Isolation of Host‐Habitat Seeking Stimulant

Abstract: The main point of the present study is the isolation of pigeon pea leaf‐oil, isolated from the fresh leaves of Cajanus cajan. This oil was found to lure the parasitoid towards the source at very low concentration (0.025%) indicating that either the oil itself functions as allomones or certain active gradients are dissolved in it. The parasitoid Trioxys (Binodoxys) indicus parasitoidises the pigeon pea aphid Aphis craccivora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
1992
1992

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…Initially, L. rnirzui might be attracted towards its host habitat (food plant) under the influence of allomones and then to the hosts (aphid) under the influence of kairomones (PANDEY et al 1982). Several authors have also reported the role of plant volatiles that attract the parasitoids (BROWN et al 1970;READ et al 1970;SCHUSTER and STARKS 1974;SINGH and SINHA 1982;POWELL and ZHI-LI 1983;PANDEY and SINGH 1986). ALTIERI et al (1981) have demonstrated the stimulatory activity of the water extracts of the food plant upon the fecundity of the parasitoids.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, L. rnirzui might be attracted towards its host habitat (food plant) under the influence of allomones and then to the hosts (aphid) under the influence of kairomones (PANDEY et al 1982). Several authors have also reported the role of plant volatiles that attract the parasitoids (BROWN et al 1970;READ et al 1970;SCHUSTER and STARKS 1974;SINGH and SINHA 1982;POWELL and ZHI-LI 1983;PANDEY and SINGH 1986). ALTIERI et al (1981) have demonstrated the stimulatory activity of the water extracts of the food plant upon the fecundity of the parasitoids.…”
Section: Resultsmentioning
confidence: 99%
“…(3) the potential of the parasitoids is affected by the type of food consumed by the hosts (Greenblatt & Barbosa, 1980;Bhatt & Singh, 1989); parasitoids/hyperparasitoids are influenced by plant characteristics; certain plants produce chemical repellents or physical deterrents to entomophagues and a suitable host feeding on such plants may escape parasitism (Vinson, 1981;Singh & Bhatt, 1988). Plant volatiles also attract the natural enemies of insects (Read et al, 1970;Elzen er al., 1984;Pandey & Singh, 1986) and reinforce their activities on the source and increase the rate of parasitism (Altieri et al, 1981); and (5)=the texture of the leaf surface plays a major role in the movement of the insects, thereby affecting the rate of oviposition (Obrycki, 1986). Thus it is clear that the efficiency of the hyperparasitoid may be influenced by all the trophic levels below it, in a similar way to that of parasitoids (Price, 1986).…”
Section: Axunthopsis (Ashmead) (Andrews 1978) Andmentioning
confidence: 99%